Variation in buccal surface morphology of deciduous first molars - M Simratvir; G Moghe; D Singh; K Dhillon (Wolters Kluwer Medknow Publications, 2012)
Background: The buccal bulge of the deciduous first molars has always been a restorative challenge to the pediatric dentist. Morphologically it may vary from a slight prominence to a well-developed cusp-like structure. Aim: This study was conducted to determine the variable buccal surface morphology of deciduous first molar and its clinical relevance. Materials and Methods: A prospective study was conducted whereby 2016 patients visiting the outpatient clinic of dental hospital over 1 year were evaluated. Any variation in buccal surface morphology of the deciduous first molars was recorded photographically or by replicating in dental stone. Results: Varied morphological patterns on buccal surface were observed for which a new classification scheme has been proposed. Conclusion: The surface morphology of deciduous teeth crowns must be studied carefully as it may be indicative of pulpal extensions and accessory roots, requiring consideration during restorative treatment planning.